Effects of Acute Creatine Supplementation on Resting Muscle Protein Fractional Synthetic Rate - Parise, Gianni (My University, 1999)
Background & Rationale: During high intensity muscle contractions phosphocreatine is enzymatically degraded by creatine kinase (CK) to form creatine and the free energy which is released used to phosphorylate ADP to ATP. Creatine is then rephosphorylated during periods of relative ATP abundance (ie. rest) by CK back to phosphocreatine. Recognition of the importance of the phosphocreatine system to energy transduction has led many to believe that creatine monohydrate supplementation, which may lead to increases in phosptocreatine (PCr), may be beneficial during high intensity exercise. Several studies have demonstrated that creatine monohydrate supplementation for as few as three days can result in significant performance gains during exercise such as sprinting, or a weight lifting program. A common observation during these studies is a 1-2 kg increase in lean body mass (LBM). Although most researchers have speculated that this increase in LBM is due to water retention, some 𝘪𝘯 𝘷𝘪𝘵𝘳𝘰 work has demonstrated that creatine may stimulate protein synthesis. The purpose of this investigation was to examine whether a loading dose of creatine (20g/d x 7d) would have any affect on mixed muscle protein synthesis (MPS) in resting human skeletal muscle. Methods: A total of 22 young healthy subjects (n = 11 male, n = 11 female) were included in the study. On the day of measurement, subjects were provided with a meat free pre-packaged diet that was based upon individual diet records. Measurements of mixed muscle protein fractional synthetic rate (FSR) were completed over a 14 h resting period using a primed constant infusion of L[1-¹³C]leucine and muscle biopsies of 𝘲𝘶𝘢𝘥𝘳𝘪𝘤𝘦𝘱𝘴 𝘧𝘦𝘮𝘰𝘳𝘪𝘴 at isotopic plateau. Subjects were then randomly assigned to either a creatine (20g/d x 7d) or a placebo (isoenergetic glucose polymer) group. Following 7 days of supplementation, subjects reported to the lab under the same conditions as in the pre-trial, and resting mixed muscle protein FSR was again determined. Results: There were no significant between group differences in the baseline subject characteristics. No significant difference in FSR was observed with regards to condition (Pl: pre-0.63 ± 0.02 %/h; pst-0.71 ± 0.016 %/h; Cr: pre-0.56 ± 0.02 %/h; pst-0.58 ± 0.023 %/h) (creatine supplementation), time, or gender (Males: pre-0.06 ± 0.02 %/h; pst-0.068 ± 0.023 %/h; Females: pre-0.057 ± 0.02 %/h; pst-0.058 ± 0.015 %/h) Creatine supplementation resulted in a 13.1% increase in total creatine, however, no significant increases; in PCr or free Cr were observed. Similarly, no significant increases for fat free mass (FFM), or total mass were observed. Conclusion: It is concluded that creatine monohydrate supplementation for 7 d at 20g/d significantly increases muscle total creatine concentration, however, does not significantly affect muscle protein FSR in males or females.
Keywords: creatine; muscle; protein; synthetic